Recurrent ischemic stroke: Incidence, predictors, and impact on mortality - Khanevski, Andrej Netland (Acta Neurol Scand, 2019)
BACKGROUND AND PURPOSE: Recurrent ischemic stroke (IS) or TIA is frequent with a considerable variation in incidence and mortality across populations. Current data on stroke recurrence and mortality are useful to examine trends, risk factors, and treatment effects. In this study, we calculated the incidence of recurrent IS or TIA in a hospital‐based stroke population in Western Norway, investigated recurrence factors, and estimated the effect of recurrence on all‐cause mortality. METHODS: This prospective cohort study registered recurrence and mortality among 1872 IS and TIA survivors admitted to the stroke unit at Haukeland University Hospital between July 2007 and December 2013. Recurrence and death until September 1, 2016, were identified by medical chart review. Cumulative incidences of recurrence were estimated with a competing risks Cox model. Multivariate Cox models were used to examine recurrence factors and mortality. RESULTS: During follow‐up, 220 patients had 277 recurrent IS or TIAs. The cumulative recurrence rate was 5.4% at 1 year, 11.3% at 5 years, and 14.2% at the end of follow‐up. Hypertension (HR = 1.65, 95% CI 1.21‐2.25), prior symptomatic stroke (HR = 1.63, 95% CI 1.18‐2.24), chronic infarcts on MRI (HR = 1.48, 95% CI 1.10‐1.99), and age (HR 1.02/year, 95% CI 1.00‐1.03) were independently associated with recurrence. A total of 668 (35.7%) patients died during follow‐up. Recurrence significantly increased the all‐cause mortality (HR = 2.55, 95% CI 2.04‐3.18). CONCLUSIONS: The risk of recurrent IS stroke or TIA was modest in our population and was associated with previously established risk factors. Recurrence more than doubled the all‐cause mortality.